13.1k views
4 votes
Explain the difference between – 2 3 and (-2)'. Be specific and write incomplete sentences.

Explain the difference between – 2 3 and (-2)'. Be specific and write incomplete sentences-example-1

1 Answer

3 votes

Step-by-step explanation

Step 1

you have to keep in mind that when you use parentheses the negative symbol is also raised to the power


\begin{gathered} -2^3=-(2^(^3))=-(2\cdot2\cdot2)=-(8)=-8 \\ \text{and} \\ (-2)^3=-2-2-2=(-\cdot-\cdot-)(2\cdot2\cdot2)=-8 \end{gathered}

User Navdroid
by
5.0k points